2022
DOI: 10.5115/acb.22.200
|View full text |Cite
|
Sign up to set email alerts
|

The ameliorating role of sofosbuvir and daclatasvir on thioacetamide-induced kidney injury in adult albino rats

Abstract: Thioacetamide (TAA) exposure and hepatitis C virus infection are usually associated with renal dysfunction. Sofosbuvir (SFV) and daclatasvir (DAC) drugs combination has great value in the treatment of hepatitis C. The study aimed to identify the nephrotoxic effects of TAA and to evaluate the ameliorative role of SFV and DAC in this condition. Forty-eight adult male albino rats were divided into eight groups and received saline (control), SFV, DAC, SFV+DAC, TAA, TAA+SFV, TAA+DAC and TAA+SFV+DAC for eight weeks.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…SOF had been reported to induce massive tubular vacuolation in association with congested glomerular capillaries in previous studies [ 35 , 45 ]. However, it partially improves renal architecture damage induced by thioacetamide when it combined with declatasvir [ 46 ]. Multiple atretic follicles and dilated congested blood vessels were also demonstrated in the SOF treated group and the number of those atretic follicles were significantly higher in the drug treated group compared to the control.…”
Section: Discussionmentioning
confidence: 99%
“…SOF had been reported to induce massive tubular vacuolation in association with congested glomerular capillaries in previous studies [ 35 , 45 ]. However, it partially improves renal architecture damage induced by thioacetamide when it combined with declatasvir [ 46 ]. Multiple atretic follicles and dilated congested blood vessels were also demonstrated in the SOF treated group and the number of those atretic follicles were significantly higher in the drug treated group compared to the control.…”
Section: Discussionmentioning
confidence: 99%
“…Besides its toxic effects on the liver, TAA is known to cause blood abnormalities, lipoprotein abnormalities [ 37 ], and kidney disorders [ 38 ]. Contrary to the present study, studies have reported that TAA causes a decline in the levels of RBCs and HB and an increase in WBC levels due to acute inflammation in response to chemicals such as TAA [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%